The 2012 Emilia earthquake (Italy): Geotechnical characterization and ground response analyses of the paleo-Reno river levees. Issue 86 (July 2016) - Facciorusso, Johann; Madiai, Claudia; Vannucchi, Giovanni
Abstract: In 2012 Northern Italy was hit by a seismic sequence with earthquakes of moderate local magnitudes and shallow hypocentral depths. After the main shocks of May 20, collapse of buildings and lifeline ruptures were widely observed in the epicentral area within a distance of about 15 km, where large acceleration values with prevailing vertical component were recorded. Locally, at a greater distance, intense and spectacular liquefaction effects were observed. They mainly affected the earthen embankments of the old Reno river channel (paleochannel), and, to a lesser extent, their immediate surroundings. In these far-field areas, ground surface accelerations were significantly low and not consistent with the spreading and extent of the observed liquefaction effects. A detailed geotechnical survey was performed to identify depth, location and behaviour of liquefied soil layers and to analyse their influence on ground response and surface liquefaction effects. Results from in situ and laboratory tests, performed under static and dynamic loading conditions, are presented herein and a complete geotechnical model of the ancient levees and the underlying soil deposit is proposed for numerical site-specific seismic analyses. More attention was paid to analysing the influence of non-linear behaviour of interbedded liquefied sands on the expected surface ground motion. Implications and limits of the results obtained are discussed with, finally, proposals for adjustments to 1-D linear equivalent models operating in the frequency domain, for taking into account stiffness degradation of liquefiable layers at high strain levels. Highlights: A reliable geotechnical model of old Reno river paleochannel is proposed. Non-linear soil behaviour when approaching failure is discussed. Influence of non-linear behaviour of liquefied soils on ground motion is evaluated. Results, implications and limits of local seismic response analyses are discussed. Adjustments to 1-D linear equivalent models are proposed.